FAKTOR-FAKTOR YANG MEMPENGARUHI LABA BERSIH - Anggadini, Sri Dewi (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2018)
This research empirically examines partially the influence of operating cost and inventory turnover to net income and conducted on the food and baverages companies listed in Indonesian stock exchange period 2011-2015. The problems that occur are the decrease of net income despite the operating cost are decrease inventory and turnover are increased. This research uses descriptive analysis verification with the unit of analysis in this research is financial statement of the food and bavarages companies listed in Indonesian stock exchange period 2011-2015. And the population is 70 financial statements from 14 companies with sample select by using purposive sampling so obtained samples is 45 financial statements from 9 companies. Data analysis technique used is multiple linear regression analysis and helped by using application program SPSS statistics version 16. These results indicate that net income is influenced by operating cost with negative related, and inventory turnover is influenced with positive related. Partially inventory turnover has more dominant influence than the operating cost.